PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NONMANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aditama, Ferry; Purwaningsih, Anna (Modus Journals, 2014)
This study aim to assess and obtain empirical evidence about the efect of tax planning on earnings management practices seteleh the change (decrease) in single tax rate in 2010 on the non-manufacturing companies listed on the Indonesia Stock Exchange. Effect of tax planning on earnings management is also associated with the phenomenon of change (decrease) in tax rates that began in the 2010 tax year. Tis study used a sample of 77 non-manufacturing companies listed in Indonesia Stock Exchange in 2009-2012. This research using descriptive statistics and simple linear regression for data analysis. The dependent variable in this study is earnings management, whereas the independent variable in this study is tax planning. Based on the results of data analysis, it appears that it was not tax planning manajamen positive efect on earnings in non-manufacturing companies listed on the Stock Exchange. However, the results of the descriptive analysis showed that 77 companies sampled in this study do tax planning in a way to avoid a decrease in profit.Keywords : earning management, earning threshold, tax planning, taxation.